Comparison of fast single-molecule experiments and simulation of translocation through the SecY translocon. - Tsybulskyi, Volodymyr (Jihočeská univerzita, 2018)
I have developed a computational package using novel Monte Carlo 1D approach to test current hypotheses of SecYEG translocation against available experimental data. I have also introduced new correlative approach using Protein Structure Networks to process data from molecular dynamics, which will improve success rate in design of future fluorescence experiments in the Laboratory of Single Molecule Fluorescence.
Comparison of fast single-molecule experiments and simulation of translocation through the SecY translocon.
Keywords: protein translocation; simulation; SecYEG; 1D Brownian model; molecular motors; protein translocation; simulation; SecYEG; 1D Brownian model; molecular motors